Multiple Septal Coronary‐Cameral Fistulae after Septal Myectomy. Issue 11 (8th June 2015) - Al Maluli, Hayan; Mathur, Moses; Keane, Martin G.; Guy, T. Sloane; Dries, Daniel; Edmundowicz, Daniel
Mini‐Abstract: Coronary‐cameral fistulae are rare after septal myectomy. Although most close spontaneously, their recognition is important as they may become clinically relevant if they persist.